The Relationship of Safety Knowledge and Safety Skills with Safety Behavior in Chemical Manufacturing Companies - Azielia, Zanifa; Dwiyanti, Endang (Fakultas Ilmu Kesehatan, 2024)
Work accidents that occur in the workplace can harm workers and companies both materially and non-materially and temporarily or permanently. Workplace accidents are unwanted events that can cause physical injury to a person even fatal to death or lifelong disability and property damage. The main cause of accidents in the workplace is due to a lack of knowledge, skills and other factors from within the individual who will eventually tend to behave unsafely at work. This study is quantitative research with research type observational analytical research with a cross-sectional design. This study employed a total population sampling method, including all 35 participants from X Company and residents of the Z Plant area, conducted during March to April 2024. Data were collected through questionnaires and interviews. Spearman correlation analysis was used to assess the strength of the relationship. The results showed that the strong relationship between knowledge (r = 0.377) with safety behavior was in the low category. While the strong relationship between skills (r = 0.470) with safety behavior is in the medium category.